Analysis and implications of communication, competence, and workload on the performance of regional financial agencies in parepare city - Arfandy Dinsar; Irawati Nur; Sulawati; Nabila Amanda Pratiwi (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This research was conducted with the aim of knowing and analyzing the influence of communication, competence and workload on the performance of the Regional Financial Agency of Parepare City. This study uses a qualitative and quantitative approach to determine the causal relationship (influence) between the independent and dependent variables. This research was conducted at the Regional Finance Agency of Parepare City. This study was conducted for approximately two months, from May to July 2025. The population and sample in this study were 72 civil servants. The results of this study indicate that communication (X1) with tcount 2.182 > ttable 1.995 and a significant level smaller than 0.05 (sig = 0.030 < 0.05), it can be said that communication (X1) has a positive and significant effect, competence (X2) with t count 2.246 > t table 1.995 and a significant level smaller than 0.05 (sig = 0.015 < 0.05), it can be said that competence (X2) has a positive and significant effect. workload (X3) with t count 3.880 > t table 1.995 and a significant level smaller than 0.05 (sig = 0.000 < 0.05), it can be said that workload (X3) has a positive and significant effect. The calculated F result is 89,270 > F table, which is 2.74 with a probability value of 0.000, which means it is below the significance value of 0.05.. Keywords: Communication, Competence, Workload and Performance